Advanced control strategies for microgrids: A review of droop control and virtual impedance techniques - K.N. Yogithanjali Saimadhuri; M. Janaki (Results in Engineering)
In microgrids, stability is ensured by maintaining a power ratio that balances total energy production and demand via coordinated management of various distributed generation (DG) units. In recent years, there has been intense research on incorporating advanced techniques into control methods for microgrids. However, a thorough examination of the hierarchical control methods for various microgrid topologies is rarely addressed. Specifically, the interplay between control methodologies namely centralized, decentralized, and distributed across AC, DC, and hybrid microgrids has not been thoroughly explored. This study fills that gap by offering a comprehensive overview of microgrid architectures and hierarchical control methods, with a special emphasis on their application to various topologies. In contrast to previous studies, this study critically investigates how two popular control strategies namely droop control and virtual impedance strategies are implemented in parallel-connected inverters for efficient power sharing. We also highlight various approaches, challenges, limitations, advancements and a comparative analysis to direct further study and real-world implementations. This review is a helpful resource for researchers and practitioners looking to improve the stability and efficiency of microgrid systems using novel control techniques.